Hubungan Unsafe Action dan Unsafe Condition dengan Kecelakaan Kerja pada Pekerja Industri Mebel - Adhwa Umniyyah Danur Irkas; Azizah Musliha Fitri; Ayu Anggraeni Dyah Purbasari; Terry Y.R. Pristya (Jurnal Kesehatan, 2020)
The furniture industry was one of many industries that are necessities part of human life. The purpose of this study was to analyze the relationship between age, length of work, hours of work, OSH knowledge, unsafe action, and unsafe condition with workplace accidents in furniture industry workers in the Duren Sawit Subdistrict in 2020. The method used in this study was a quantitative analysis method with a cross-sectional study design. The sample in this study were 57 workers. The result obtained using the chi-square test was the variable age, hours of work, and unsafe condition found the value of p-value>0,05 or there was not any relationship. The variable length of work, OSH knowledge, and unsafe action obtained value of p-value<0,05 or there was a relationship. The recommended action for workers and shop owners is to increase awareness in using PPE when working, always maintain cleanliness and implement OSH behavior in the workplace, always obey the rules and remind each other if there are workers who do not obey the rules, and always maintain tidiness at the place and make workplace cleaning efforts more routine.